Pedagogical possibilities for further improving physical culture in the development of a healthy lifestyle for talented girls in higher education institutions - Dilafruz Nishonova (Zien Journals, 2022)
This article has approved the main guidelines for physical culture in the development of a healthy lifestyle for high school students, and some of the problems have been investigated on the basis of a special questionnaire.
Keywords: Student girls; physical well-being; daily lifestyle; level of physical culture